Materials for Energy Infrastructure - Udomkichdecha, Werasak; Mononukul, Anchalee; Böllinghaus, Thomas; Lexow, Jürgen (Springer Nature Singapore : Imprint: Springer, 2016)
This book presents contributions to the topics of materials for energy infrastructure with a focus on data and informatics for materials. This spectrum of topics has been chosen because challenges in terms of materials are identified to lie in transport and storage of energy, adequate supply of food and water, well-working infrastructure, materials for medical application and health, efficient use of scarce resources or elements and alternate materials solutions as well as recycling. The contributions were invited at the 4th WMRIF Young Materials Scientist Workshop held at the National Institute for Standards and Technology (NIST) in Boulder, Colorado, USA during September 8-10, 2014.  .